Canons 125, 126, and 273: Mandatory Psychological Testing - Austin, Brian T. ca. 20./21. Jh. (2021)
Can a diocesan bishop or major superior of a clerical institute of pontifical right oblige a cleric to undergo psychological testing in virtue of their "special obligation" of obedience ( c. 273)? If a cleric's consent is extorted through force or fear ( c. 125), or if he did not know or understand what he was consenting to ( c. 126), can the ordinary licitly retain or use the psychological evaluation?